The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/ece3.1450
|View full text |Cite
|
Sign up to set email alerts
|

Offspring size at weaning affects survival to recruitment and reproductive performance of primiparous gray seals

Abstract: Offspring size affects survival and subsequent reproduction in many organisms. However, studies of offspring size in large mammals are often limited to effects on juveniles because of the difficulty of following individuals to maturity. We used data from a long-term study of individually marked gray seals (Halichoerus grypus; Fabricius, 1791) to test the hypothesis that larger offspring have higher survival to recruitment and are larger and more successful primiparous mothers than smaller offspring. Between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(136 citation statements)
references
References 64 publications
6
129
1
Order By: Relevance
“…Previous work across a variety of species has demonstrated that offspring weaning mass is positively associated with both juvenile survival (Wauters, Bijnens & Dhondt ; McMahon, Burton & Bester ; Ailsa, Bernie & Barker ; Côté & Festa‐Bianchet ; Proffitt, Garrott & Rotella ) and future reproductive success (Festa‐Bianchet, Jorgenson & Réale ; Bowen et al . ). Our results imply that the pups with the highest weaning mass are born to experienced, prime‐aged and older mothers with above‐average individual effect on parturition masses and daily mass gains through the lactation period.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work across a variety of species has demonstrated that offspring weaning mass is positively associated with both juvenile survival (Wauters, Bijnens & Dhondt ; McMahon, Burton & Bester ; Ailsa, Bernie & Barker ; Côté & Festa‐Bianchet ; Proffitt, Garrott & Rotella ) and future reproductive success (Festa‐Bianchet, Jorgenson & Réale ; Bowen et al . ). Our results imply that the pups with the highest weaning mass are born to experienced, prime‐aged and older mothers with above‐average individual effect on parturition masses and daily mass gains through the lactation period.…”
Section: Discussionmentioning
confidence: 97%
“…Blubber thickness of hunted adult females also partly explained the variation in the birth rate of gray seal females (birth rate from Kauhala et al 2016: Table 2; r 2 = 0.53, F = 8.9, df = 1, 6, p = 0.024) in recent years. Nutritional status (or body mass) of female seals may thus have an impact on reproduction (age at sexual maturity, ovulation rate, implantation of embryos, and maintenance of pregnancy) of seal females (e.g., Boyd 1984;Boyd et al 1999;Harwood et al 2000;Bowen et al 2006Bowen et al , 2015.…”
Section: Importance Of Herring Quality On Baltic Gray Sealsmentioning
confidence: 99%
“…Average thickness of the blubber layer in a population varies between years with environmental conditions and can be used as an index of nutritional status of seals. Blubber layer and weight of pups of the year are closely correlated to their subsequent first year survival (Hall et al 2001;Harding et al 2005) but also have delayed effects influencing age at sexual maturity and size at first parturition of female seals (Boyd et al 1999;Bowen et al 2015). Blubber thickness may also affect reproductive rate of mature females through implantation of embryos and fetal mortality (e.g., Boyd 1984).…”
Section: Introductionmentioning
confidence: 99%
“…All models having a ∆AIC c <2 were considered as having some support, but we preferred models with the fewest parameters and the highest weight and, therefore, highest evidence ratio (Burnham & Anderson ; Bowen et al. ). The effect size ( r‐ value) was calculated using the z ‐statistic for each predictor variable, such that the covariates were taken into account.…”
Section: Methodsmentioning
confidence: 99%